Assessment of solid waste generation and treatment in the Australian economic system: A Closed Waste Supply-Use model. (August 2018) - He, He; Reynolds, Christian John; Boland, John
Highlights: A closed waste supply-use (CWSU) model for waste estimates is proposed. Applying CWSU model to analyse effects of the Household sector on waste flow. Waste generation effects are discussed in an Australian case study. Mixed flows of the Household sector are displayed. Abstract: The Household sector (HS) is not only the major cause of waste generation in industrial sectors, but also the same function as an industrial sector to generate waste. Current researches mainly focus on waste generation caused by the demand of the HS based on the environmentally-extend input-output (EEIO) models while the effect of the HS as an industrial sector on waste flow has not been analysed. In addition, there is uncertainty around the economic cost of waste management discussed in EEIO models due to the lack of the calculation of the cost of labor. We adjust waste supply-use table to analyse effects of the HS as an industrial sector on waste flow, resulting in closed waste supply-use table (CWSUT). The novelty of the method lies in a shift in the effect of the HS, from an exogenous factor to an endogenous factor. Results derived from Australian CWSUT in 2009–10 illustrate waste generation effects of intermediate sectors and the mixed waste flows of the HS. The definition of "intermediate sector" is that the sector consumes intermediate inputs from producing sectors and generates intermediate outputs to Final demand. They show that: (1) the Construction sector has the largest waste generation effects, in which the amount of masonry waste has accounted for the most direct and total effects of waste generation; (2) investigations regarding the HS in CWSUT can calculate the amount of direct and total waste generation, the monetary flow, and effects of the Income for the Household sector. Base on the above results, the paper puts forwards the application of the CWSUT on other types of environmental issues and waste policies.